Pengaruh Logam Berat Terhadap Karang - Wicaksono, Denrishaq Budi; Yulianto, Bambang; -, Ambariyanto (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Coral reefs are known as complex marine ecosystems. They play essential role in sustaining life. These ecosystems can serve as conservation areas as well as marine tourism object. The condition of coral reef degradation in Indonesia is quite worrying. One contributing factor is increasing heavy metal pollution in the waters. Levels of heavy metals that exceed the quality standard are very harmful to coral reefs. Heavy metals can not be degraded in waters but can be absorbed. Considering the importance of coral reef ecosystems and the increasing number of heavy metal pollution, it is necessary to know the effect of heavy metals on Corals. In general, the effect of heavy metals on corals can be divided into two, effects that did not cause of death (sublethal) and cause of death (lethal).